2017
DOI: 10.1111/cpf.12495
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and methodological aspects of rate of force development assessment in human skeletal muscle

Abstract: Rate of force development (RFD) refers to the ability of the neuromuscular system to increase contractile force from a low or resting level when muscle activation is performed as quickly as possible, and it is considered an important muscle strength parameter, especially for athletes in sports requiring high-speed actions. The assessment of RFD has been used for strength diagnosis, to monitor the effects of training interventions in both healthy populations and patients, discriminate high-level athletes from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
162
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(175 citation statements)
references
References 237 publications
(562 reference statements)
6
162
1
6
Order By: Relevance
“…In addition, these were focused on RFD during isometric contractions with a few exceptions focusing on RFD during dynamic movements, in any case with maximal effort, only [43,44]. An isolated report suggested that RFD is rather constant once 30% or more of the maximal force is required [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these were focused on RFD during isometric contractions with a few exceptions focusing on RFD during dynamic movements, in any case with maximal effort, only [43,44]. An isolated report suggested that RFD is rather constant once 30% or more of the maximal force is required [45].…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant decline in early and late RFDr (30-200 ms) along 5 minutes after the exercise protocol, independently of blood flow condition. The decline in the early phase of RFDr (i.e, < 100ms) along the five minutes after the IIHE may be justified by alterations in neural factors such as reduction of the motor unit discharge rate 15,16 . Although the applied protocol has no features to induce changes in muscle structure properties, the decrease in the late RFDr after TF may relate to impairment of cross-bridge kinetics 13,28,29 imposed by the accumulation of metabolites, as well as the exercise-induced reactive oxygen/nitrogen species production in the muscle fiber 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The RFD, which is derived from the force-or torque-time curves recorded during maximal voluntary contractions 14 , have been increasingly used to characterize the capacity for rapid muscle force production in populations including athletes and frail elderly patients 15 . Among reasons for this interest are the facts that (1) it is sensitive to detect acute and chronic changes in neuromuscular function 15 , (2) estimate the degree of fatigue and recovery after acute exhausting exercise 16 and (3) be potentially governed by different physiological features 15,17 , such as neural and muscular (viz., peripheral) mechanisms. Despite the peak force, defined as the maximum force achieved during a maximal muscle effort, independently of the time to achieve it, be a widely used parameter to study muscle performance, there are some limitations with this parameter, when the aim is to investigate the mechanisms involved in the muscle force production capacity 18 , when compared to the RFD.…”
Section: Introductionmentioning
confidence: 99%
“…23 RFD reflects the ability to produce a high rate of rise in muscle force per unit of time following contraction onset, which can be measured during isometric contraction conditions using force-time or torque-time curves and calculating the average tangential slope between given time points on the curve (eg, at 0-50 ms). 39 In typical activities of daily living (eg, descending stairs, walking fast, or reversing a fall) and athletic movements (eg, sprinting, kicking, and jumping), short-duration muscle contraction times of 50-200 ms are often observed. 39,40 However, when obtained at standardized isometric and optimal length-tension conditions maximal voluntary contraction (MVC) force is not reached until 300-500 ms from the onset of the contraction.…”
Section: Introductionmentioning
confidence: 99%
“…39 In typical activities of daily living (eg, descending stairs, walking fast, or reversing a fall) and athletic movements (eg, sprinting, kicking, and jumping), short-duration muscle contraction times of 50-200 ms are often observed. 39,40 However, when obtained at standardized isometric and optimal length-tension conditions maximal voluntary contraction (MVC) force is not reached until 300-500 ms from the onset of the contraction. 41 Notably also, the time to reach joint angle and angular velocity-specific MVC torque is shorter for concentric vs eccentric and isometric contractions and decreases as a function of contractile speed.…”
Section: Introductionmentioning
confidence: 99%